Sugar Content Composition of Various Types of Honey Produced by Apis Mellifera L.: A Review - Waworuntu, Juniarny (Jurnal Penelitian Pendidikan IPA, 2024)
The purpose of this review is to determine the sugar content profile in various types of honey produced by Apis mellifera, such as monofloral, unifloral, extra-floral, and honeydew. Generally, the goal is to assess the average sugar content parameters within acceptable ranges set by SNI, Codex, and EU as quality and sugar content requirements. Among the honey types studied, monofloral honey met the sugar standards but some samples were found to have low sugar content, ranging from 21.77% to 58.95%, below SNI and Codex standards. In contrast, unifloral, extra-floral, and honeydew honeys exhibited higher sugar levels, in accordance with established standards, ranging from 73.40% to 83.9%. The differences in sugar content among the types of honey produced by A. mellifera are influenced by nectar sources, geography, climate, and vegetation. Monofloral honey tends to have lower sugar content, while unifloral, extra-floral, and honeydew honeys are richer in sugar, making them more compliant with honey quality standards. Further research should focus on identifying plant species and the quantity of nectar that can consistently produce honey with sugar content meeting established quality standards.